Substrate temperature effects on infrared emissivity of TiNx films. (2nd January 2019) - Lu, Linlin; Luo, Fa; Huang, Zhibin; Zhou, Wancheng; Zhu, Dongmei
ABSTRACT: TiN x films were deposited using direct current reactive magnetron sputtering on glass substrates, and the variation of resistivity and infrared emissivity of TiN x films deposited at different substrate temperatures was investigated. The N/Ti ratios of prepared films were off-stoichiometric, and reached the highest value 0.97 at 350°C. The results showed that substrate temperature had an important role in regulating the resistivity and infrared emissivity of TiN x films, and the change in resistivity of the films was consistent with their infrared emissivity. As the substrate temperature increased from 25 to 350°C, the resistivity of the films decreased from 15.7 × 10 3 to 0.9 × 10 3  μΩ cm. Infrared emissivity in the wavelength of 3–5 μm decreased from 0.55 to 0.29, and the value in the wavelength of 8–14 μm dropped from 0.54 to 0.27.